Patient‐reported outcomes in cirrhosis: A scoping review of the literature. Issue 6 (19th April 2018) - Tapper, Elliot B.; Kanwal, Fasiha; Asrani, Sumeet K.; Ho, Chanda; Ovchinsky, Nadia; Poterucha, John; Flores, Avegail; Smith, Judith E.; Ankoma‐Sey, Victor; Luxon, Bruce; Volk, Michael L.
Abstract : Patients with cirrhosis seek improvement in their symptoms, functioning, quality of life, and satisfaction with the care they receive. However, these patient‐reported outcomes (PROs) are not routinely measured for clinical care, research, or quality improvement. The members of the American Association for the Study of Liver Diseases Practice Metrics Committee, charged with developing quality indicators for clinical practice, performed a scoping review of PROs in cirrhosis. The aim is to synthesize a comprehensive set of PROs for inclusion into a standard patient‐centered outcome set. We searched Medline, Embase, the Cumulative Index to Nursing and Allied Health Literature, PsycINFO, and the Cochrane Trial Library since inception, with final searches run between April 20 and June 1, 2017. Studies were included if they reported the construction and/or validation of a PRO instrument for patients with cirrhosis or if they assessed the clinical (case‐mix) variables determining responses to established PRO scales. Eleven studies were selected that yielded 259 items specific to patients with cirrhosis. After removing duplicates, 152 unique items were isolated. These items were consolidated into seven domains: physical symptoms, physical function, mental health, general function, cognition, social life, and satisfaction with care. The seven domains included 52 subdomains (e.g., physical domain, abdominal pain subdomain). Twelve variables were identified that independently modified established PRO scales. These included clinical factors (severity of liver disease and its complications, medication burden, and comorbidities), specific PROs (cramps, pruritis), and surrogate outcome measures (falls, hospitalization). Conclusion: This scoping review identified and categorized a large existing set of PRO concepts that matter to patients with cirrhosis; these outcomes may now be translated into usable measures both for the assessment of the quality of cirrhosis care in clinical practice and to perform research from the patient's perspective. (Hepatology 2018;67:2375‐2383).